2005
DOI: 10.1002/arch.20047
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of odorant-binding proteins of the malaria-carrying mosquitoesAnopheles gambiae andAnopheles arabiensis

Abstract: Host preference and blood feeding are restricted to female mosquitoes. Olfaction plays a major role in host-seeking behaviour, which is likely to be associated with a subset of mosquito olfactory genes. Proteins involved in olfaction include the odorant receptors (ORs) and the odorant-binding proteins (OBPs). OBPs are thought to function as a carrier within insect antennae for transporting odours to the olfactory receptors. Here we report the annotation of 32 genes encoding putative OBPs in the malaria mosquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…However, their respective orthologous genes in An. gambiae , AgamOBP11 and AgamOBP29, were classified as “classic” OBPs in previous studies [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, their respective orthologous genes in An. gambiae , AgamOBP11 and AgamOBP29, were classified as “classic” OBPs in previous studies [17].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we found that the most abundant Obp transcript in the antenna, Obp19d , is expressed in epidermal cells and not accessory cells, consistent with the findings of (Park et al, 2000), and is thus unlikely to be secreted into sensillar lymph. It seems plausible that Obp19a binds ligands other than odorants, as may other Obps that are expressed outside the olfactory system (Arya et al, 2010; Li et al, 2005; Pitts et al, 2014). Not only are Obps highly diverse, but sensilla also are diverse in structure and function, as illustrated by the lack of visible pore tubules in trichoid sensilla of Drosophila (Shanbhag et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of OBPs present within a variety of insect species [13] and identification of genes encoding OBPs has been mainly by means of bioinformatic approaches based on the characteristic features of the protein families [2430]. These features include the six-cysteine OBPs signature, a size of 15–20 kDa, the α-helix pattern, the globular water-soluble nature and the presence of a signal peptide.…”
Section: Introductionmentioning
confidence: 99%